Fluoroscopy based needle-positioning system for percutaneous nephrolithotomy procedures - Conradie, Jean-Pierre (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--Stellenbosch University, 2008.